Very early feeding in stable small for gestational age preterm infants: a randomized clinical trial - Shmuel Arnon; Daniella Sulam; Fred Konikoff; Rivka H. Regev; Ita Litmanovitz; Timna Naftali (Elsevier, 2013)
Objective: To examine the effect of initiating very early feeding on time-to-reach full feeding in stable, small for gestational age (SGA) preterm infants. Method: Preterm infants with gestational age below 37 weeks and birth weight below the 10th percentile were randomly allocated to a very early (within 24 hours of birth) feeding regimen or delayed (after 24 hours of birth) feeding. All infants had in utero evidence of absent or reverse diastolic flow. Infants unable to start early feeding were excluded. Time-to-reach full feeding, feeding progression, and related morbidity were compared. Electrogastrography (EGG) was used to measure pre- and postprandial gastric motility on the second and seventh day after feeding initiation. Results: Sixty infants were included in the study, 30 in each group. Infants included in the very early feeding regimen achieved full enteral feeding sooner than controls (98 ± 80-157 vs. 172 ± 123-261 hours of age, respectively; p = 0.004) and were discharged home earlier (p = 0.04). No necrotizing enterocolitis (NEC) was documented in both study groups. Gastric motility was improved at day seven after feeding initiation in both study groups, with no difference between groups. Conclusions: Stable SGA preterm infants on a very early feeding regimen achieved full enteral feeding and were discharged home significantly earlier than those on a delayed regimen, with no excess morbidity. Resumo: Objetivo: Examinar o efeito da nutrição precoce sobre o tempo para atingir a nutrição completa em neonatos prematuros (PIG) estáveis pequenos para a idade gestacional. Método: Os neonatos prematuros com idade gestacional inferior a 37 semanas e peso ao nascer inferior a 10% foram alocados aleatoriamente para um regime de nutrição precoce (nas primeiras 24 horas de vida) ou tardia (após as primeiras 24 horas de vida). Todos os neonatos apresentaram uma evidência intrauterina de fluxo diastólico reverso ou ausente. Os neonatos incapazes de iniciar uma nutrição precoce foram excluídos. O tempo para a alimentação completa, a progressão da nutrição e morbidez correspondente foram comparados. A eletrogastrografia (EGG) foi utilizada para mensurar a motilidade gástrica pré e pós-prandial no segundo e no sétimo dias após o início da nutrição. Resultados: Foram incluídos 60 neonatos no estudo, sendo 30 em cada grupo. Os neonatos incluídos no regime de nutrição precoce atingiram a nutrição enteral completa antes dos neonatos do grupo de controle (98 ± 80-157 em comparação a 172 ± 1 23-261 horas de idade, respectivamente; p = 0,004) e recebiam alta hospitalar antes (p = 0,04). Nenhuma enterocolite necrosante (ECN) foi comprovada em ambos os grupos de estudo. A motilidade gástrica melhorou no sétimo dia após o início da nutrição em ambos os grupos de estudo, sem diferença entre eles. Conclusões: Os neonatos prematuros PIG estáveis em regime de nutrição precoce atingiram alimentação enteral completa e receberam alta hospitalar significativamente antes que aqueles em regime de nutrição tardio, sem morbidez excedente. Keywords: Electrogastrography, Feeding, Preterm infants, Small for gestational age, Very low birth weight infants, Palavras-chave: Eletrogastrografia, Nutrição, Neonatos prematuros, Pequenos para a idade gestacional, Neonatos com muito baixo peso ao nascer